Omejitve pri ocenjevanju znanja matematike v gimnazijah - Jerman, Marjan (Obzornik za matematiko in fiziko, 2008)
The state regulations on the assessment of upper secondary school students (effective as from the school year 2005/06) and internal statutes of individual secondary schools limit the autonomy of teachers in some areas of student assessment. The authors wish to present how the existing solutions influence the mathematics curiculum and to initiate a reflection on the present situation and possible inprovements.
Keywords: gimnazije; matematika; ocenjevanje; poučevanje; srednje šole